USE OF DIGITAL MEDIA IN EARLY CHILDHOOD LEARNING: CASE STUDY IN PLAYGROUPS IN BANDAR LAMPUNG CITY - Reiska Primanisa; Mega Aria Monica (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the use of digital media by educators and their management strategies for effective and safe learning for early childhood playgroups. The study employed a qualitative approach with a case study design at three playgroup institutions in Bandar Lampung City. Data were collected through participant observation, in-depth interviews with principals, teachers, and parents, and documentation. Data analysis employed the Miles, Huberman, and Saldaña model, which includes data condensation, data presentation, and conclusion drawing. The results indicate that each type of digital media provides specific benefits: educational videos improve vocabulary and learning motivation; tablet applications stimulate cognitive and fine motor skills; interactive projectors encourage collaborative learning; interactive e-books strengthen early literacy; and educational audio aids children's language development and musicality. However, challenges remain, including low teacher digital literacy, limited infrastructure, the potential for excessive screen time, and a lack of institutional policy guidance. This study emphasizes the need for selecting developmentally appropriate digital media, technology-based teacher professional development, and active partnerships between Early Childhood Education institutions and parents in supervising digital media use.